THE PROBLEM OF SOCIAL PROTECTION OF CHILDREN IN THE POST-WAR PERIOD (EDUCATION IN THE 21ST CENTURY, 2024)
The implementation of social and legal protection of children in the Republic of Armenia has undergone significant improvements over the past decade, but they are still incomplete and require flexible solutions and regulation. Были внесены структурные и содержательные изменения в социальную и правовую защиту ребенка, что привело к появлению новых субъектов, пересмотру их функций, необходимости сотрудничества и другим вопросам. A unified social service and its territorial centers have been created, which will carry out a social assessment of the family, which will be taken into account when organizing the care and upbringing of a child in a difficult life situation. The implementation of social protection and fundamental rights of the child should be one of the priorities of the State. Consequently, ensuring the priority of peace in the country and the safety of the child's life, social well-being, and the best interests of the child requires a clear State policy and social and legal norms.
Keywords: Social protection of children; legislative framework; child care and protection centers; a child in an emergency situation; mass displacement; forced emigration; social security; difficult life situation